(untitled) (El-Wahat Journal for Research and Studies, 2015)
today , Real estate markets are more competitive across the country than any time ago , potential buyers are more aware , more critical and less likely to buy a partment in a real estate project without depth comparisons ,research , survey and consultate the relatives and stranges to get a result which helps the buyer to reach to the right purchase decision , as well as to reduce the expected and perceived risks from this decision , so this study comes to identify the role of reference groups , both formal and informal levels, in reducing the expected and perceived risks , whether the social or financial risks of the consumer’s decision to purchase a residential apartment in the city of Amman . identifying any of these risks have a greater impact on decision-making for purchasing residential properties and perceptions of these risks by the community study in its different demographic characteristics , data were collected by using a questionnaire which distributed to a sample included a ( 269 ) members of the apartments owners, and the study found: - There is a strong correlation between the impact of reference groups role at the formal and informal levels and reducing the social and financial perceived risks. - There are a significant statistical differences in reducing the social risk in favor of females , as there are significant statistical differences in reducing the financial risks in favor of males , - There are significant statistical differences for the reference groups role in reducing the financial perceived risks when deciding to buy residential apartments for the Jordanian consumer in Amman, these differences due to the educational level of consumer , in favor of the qualification (BA and high educations ) , as there are differences that are attributable to the monthly income average , in favor of monthly income of ( from 500-1000 JD(.